The school library of Dayspring Academy a developmental plan - Meneses, Erwina T. (2003)
A library is an integral part of a school. It is often referred to as the center of information in a school. It works hand-in-hand with schools to provide quality education and to producing information literate individuals and lifelong learners. This study aimed to develop a library for Dayspring Academy, a library wherein the school librarian works together with the faculty in teaching and imparting knowledge to the students.